Impact of Information Technology and Communication on the Performance of Nepalese Commercial Banks - Shrestha, Sangam; Pradhan, Radhe Shyam (Nepalese Journal of Finance, 2024)
The study examines the impact of information technology and communication on the performance of Nepalese commercial banks. Return on assets and net profit margin are selected as the dependent variables. The selected independent variables are automated teller machine, internet banking, mobile banking, point of sales and quick response code. The study is based on primary and secondary data of 25 commercial banks with 150 respondents. To achieve the purpose of the study, structured questionnaire is prepared. Secondary data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of information technology and communication on the performance of Nepalese commercial banks. The study showed that ATM banking has a positive impact on return on assets and net profit margin. It indicates that better the ATM banking services, higher would be the return on assets and net profit margin. Similarly, internet banking has a positive impact on return on assets and net profit margin. It indicates that better the internet banking services, higher would be the return on assets and net profit margin. Likewise, mobile banking has a positive impact on return on assets and net profit margin. It indicates that better the mobile banking services provided by the banks, higher would be the return on assets and net profit margin. In addition, point of sales banking has a positive impact on return on assets and net profit margin. It indicates that practice of point of sales banking leads to increase in return on assets and net profit margin. Moreover, QR payment has a positive impact on return on assets and net profit margin. It indicates that higher the number of payments through QR, higher would be the return on assets and net profit margin.